Perancangan Aplikasi Rumah Adat Indonesia Berbasis Android Menggunakan Augmented Reality - Mufti Mufti; Muhammad Lutfhi Hamzah; Eki Saputra; Tengku Khairil Ahsyar; Syaifullah Syaifullah (Journal of Information System Research (JOSH), 2023)
One of the materials taught in school subjects is material about traditional houses. However, in its development, many of the students did not understand and did not know about traditional houses in Indonesia because a lot of material about these traditional houses was only conveyed using books. Information and learning about traditional houses from books can only be obtained from the front view or two dimensions, this is what makes children tend to feel bored and uninterested in studying and knowing traditional houses in Indonesia. So the introduction of Indonesian traditional houses needs to be done with an application using Augmented Reality technology that is applied to Android smartphones that can help Pekanbaru 2 Vocational High School students and Android smartphone users to learn and inform about traditional houses in Indonesia. The design of this application is made using Unity and Vuforia Software. It is hoped that this application can help users easily get to know and learn about Indonesian traditional houses.